Malaysia’s relations with Saudi Arabia under Tun Dr. Mahathir era, 1981-2003 - Idris, Asmady (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia, 2010)
Malaysia’s early formal relation with Saudi Arabia begun since the late Tunku Abdul Rahman Putra al-Haj era (the first Malaysian Premier, 1957-1970) until present. During the reign of Tun Dr. Mahathir, the fourth Malaysian Premier, the relation has changed dynamically. Several initiatives have been taken by the Tun Dr. Mahathir regime to shift the pattern of relations from one to two way communication. Apart from successfully securing economic opportunities from the kingdom, this study attempts to relate the significance of the relations to the Tun Dr. Mahathir regime with its efforts to portray religious commitment, both at domestic and international level. The promotion of Islam by Malaysian leaders, both at home, and at the international level, is vital for the continuation of their political survival. Equipped with more liberal-pragmatic Islamic approach has, to some extent, prolonged the survival of the Tun Dr. Mahathir’s political regime interests.